THE NOTION OF AUTHENTICITY REVISITED A SEARCH FOR URBAN HERITAGE CONSERVATION APPROACH - Widjaja Martokusumo (TATALOKA, 2011)
During the last five decades urban heritage conservation has evolved significantly as an urban design discipline which is nec-essary for dealing with older urban areas that were once reduced to being the locus of monuments worthy of architectural conservation. Recent international experiences highlight conflicting interests in term of intention and focus, between archaeologist, who focus on monument restoration, and urban designers, who emphasize the need of conserving the spirit of the past. Nonetheless, a new understand-ing about urban heritage was materialized from the latest urban conservation praxis involving archaeologists, urban planners, urban de-signers and architects. The new insight about urban heritage has brought new approaches to urban conservation during recent decades. The latest of these approaches aim at the creation of enjoyable urban experiences that have a historical identity, rather at the simple re-tention of authentic urban history. In fact, urban heritage conservation is not simply a matter of preserving and creating harmonious constellation between historic fabrics and new infill developments, but rather a continuing project in shaping the environment. Based on several observations, this paper discusses that historic fabrics contribute considerably in place making, in enriching the quality of a place and offer opportunities for cultural appreciation. Thus, creating a sense of place is more than to the exact restoration of urban details. It also argues the importance of the making of interesting and liveable urban quarters that guarantee social, cultural and environmental sustainability.